2015
DOI: 10.1016/j.neubiorev.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal raphe nucleus projecting retinal ganglion cells: Why Y cells?

Abstract: Retinal ganglion Y (alpha) cells are found in retinas ranging from frogs to mice to primates. The highly conserved nature of the large, fast conducting retinal Y cell is a testament to its fundamental task, although precisely what this task is remained ill-defined. The recent discovery that Y-alpha retinal ganglion cells send axon collaterals to the serotonergic dorsal raphe nucleus (DRN) in addition to the lateral geniculate nucleus (LGN), medial interlaminar nucleus (MIN), pretectum and the superior collicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 181 publications
(253 reference statements)
0
14
0
Order By: Relevance
“…This was necessary because it has been reported that unlike other rodents, RGCs did not innervate the mouse DRN. However, the absence of labelled retinal fibres in the mouse DRN was based on anterograde CTB tracing24 and as recently suggested, this technique underrepresents the retinoraphe projection37, perhaps due to reduced access of the large CTB molecule at RGC branch points38. Here, we demonstrate that RGCs innervate the mouse DRN using retrograde tracing with CTB and importantly, with a modified rabies virus that restricted infection to genetically targeted DRN neurons26.…”
Section: Discussionmentioning
confidence: 52%
“…This was necessary because it has been reported that unlike other rodents, RGCs did not innervate the mouse DRN. However, the absence of labelled retinal fibres in the mouse DRN was based on anterograde CTB tracing24 and as recently suggested, this technique underrepresents the retinoraphe projection37, perhaps due to reduced access of the large CTB molecule at RGC branch points38. Here, we demonstrate that RGCs innervate the mouse DRN using retrograde tracing with CTB and importantly, with a modified rabies virus that restricted infection to genetically targeted DRN neurons26.…”
Section: Discussionmentioning
confidence: 52%
“…In the current study, evidence is provided that the retina projects directly to 5-HT and GABA neurons in the DRN. Although the gerbil retinoraphe projection is robust compared to that described for other species the number of CTB-labeled retinal processes observed in the DRN is relatively low 19 . It is very likely however, that retinal processes in the DRN are under-represented when CTB is used as an anterograde tracer.…”
Section: Discussionmentioning
confidence: 73%
“…In addition to the many glutamatergic afferents from sites in the forebrain and brainstem, the DRN also receives glutamatergic excitatory input from the retina, although details regarding DRN-projecting retinal ganglion cells (RGCs) have only recently begun to emerge 19 . RGC projections to the DRN have been described in several species including primates but have been examined most extensively in the Mongolian gerbil.…”
mentioning
confidence: 99%
“…The integrity of such causal influences is likely to underlie adaptive affective processing and states, the disruption of which could constitute the neurobiological basis for affective disorders at a more systematic level than regional abnormalities ( de Almeida et al, 2009 ). Animal studies have identified direct retino-raphe projection modulating serotonergic activity and hence affective behavior ( Ren et al, 2013 , Pickard et al, 2015 ). Research on the existence of such a direct projection in humans may help to explain how the visual environment affects mood and affective states, as seen in seasonal affective disorders.…”
Section: Discussionmentioning
confidence: 99%